Monday
March 27, 2017

Post a New Question

Posted by on .

I need to know if I am doing this problem right when sustitution method.
y+2x=3
y+2x=-4
y+2x=3 -1(y+2x=3)-y-2x=-4
now add the two equation
y-2x=3
-y-2x-4
the answer would be -4y=7
then divided -4=7 answer 1.75
I no that there is more to this answer I am just stuck and not sure if this is right are not.

  • algebra - ,

    Please only post your questions once. Repeating posts will not get a quicker response. In addition, it wastes our time looking over reposts that have already been answered in another post. Thank you.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question